Sosial Capital Analysis On Chili Farmers Group In Tanjung Pering Village Of Ogan Ilir Regency - Ramadhan, Fazri; Riswani, Riswani; Aryani, Desi (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2022)
Chili is one of the vegetable groups that has a major contribution with the highest increase in the index after shallots. This production is produced in almost every province in Indonesia. One of them is the province of South Sumatra, which is the eleventh largest chili producer in Indonesia. It was proven in 2020 according to the Central Statistics Agency that the North Indralaya sub-district had the highest large chili production in Ogan Ilir Regency reaching 5,230 than other subdistricts in Ogan Ilir Regency. Economic capital and human capital are also basic capital, with this capital humans can start carrying out economic activities, while sosial capital only benefits when interacting with sosial structures. This study aims to 1) Analyze the condition of sosial capital in chili farmer groups in Tanjung Pering Village, Ogan ilir Regency 2) Analyzing opportunities for chili farming sustainability in Tanjung Pering Village, Ogan ilir Regency 3) Analyzing the relationship of sosial capital with the sustainability of chili farming in Tanjung Pering Village, District Ogan ilir. The research method used is a survey method and sampling used in this study as many as 32 samples from 150 existing populations. The results of this study are the sosial capital of chili farmers in Tanjung Pering Village is in the medium category with an average sosial capital score of 27.20 which indicates the medium category and the sustainability of chili farmers in Tanjung Pering Village is in the currently category with an average farmer productivity is 1.59 Ton/lg and the average farmer's income is Rp. 31.034.463.54 per cultivated area per year, while the output of the Spearman rank correlation on the total sosial capital with farming sustainability is rejecting H0 which means that there is a real positive relationship between sosial capital and the sustainability of chili farming in Tanjung Pering village, North Indralaya district, Ogan Ilir district. Keyword: sosial capital, income, farmers, productivity